2012
DOI: 10.1176/appi.ajp.2011.11040551
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Contribution of Common Genetic Variants to the Risk and Pathogenesis of ADHD

Abstract: Objective:A major motivation for seeking disease-associated genetic variation is to identify novel risk processes. Although rare copy number variants (CNVs) appear to contribute to attention deficit hyperactivity disorder (ADHD), common risk variants (single-nucleotide polymorphisms [SNPs]) have not yet been detected using genome-wide association studies (GWAS). This raises the concern as to whether future larger-scale, adequately powered GWAS will be worthwhile. The authors undertook a GWAS of ADHD and examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
181
4
4

Year Published

2015
2015
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(199 citation statements)
references
References 40 publications
(49 reference statements)
6
181
4
4
Order By: Relevance
“…In accordance with the pattern seen in studies of other complex diseases shown to have a polygenic signal,18, 24, 25, 26 restricting our analysis to SNPs that met the lowest association test probability value thresholds ( p T ) in the discovery sample ( p T  < 10 −4 , p T  < 10 −3 , p T  < 0.01, p T  < 0.05) did not identify a systematic significant inflation in the polygenic scores of the PD cases of the replication samples ( p  > 0.05). Rather, our most significant evidence was observed when SNPs with p T  ≤ 0.5 in the UK sample were included where probability values for a significant inflation in the polygenic scores ranged between 4.42 × 10 −4 and 8.22 × 10 −5 (see Table 1).…”
Section: Resultssupporting
confidence: 84%
“…In accordance with the pattern seen in studies of other complex diseases shown to have a polygenic signal,18, 24, 25, 26 restricting our analysis to SNPs that met the lowest association test probability value thresholds ( p T ) in the discovery sample ( p T  < 10 −4 , p T  < 10 −3 , p T  < 0.01, p T  < 0.05) did not identify a systematic significant inflation in the polygenic scores of the PD cases of the replication samples ( p  > 0.05). Rather, our most significant evidence was observed when SNPs with p T  ≤ 0.5 in the UK sample were included where probability values for a significant inflation in the polygenic scores ranged between 4.42 × 10 −4 and 8.22 × 10 −5 (see Table 1).…”
Section: Resultssupporting
confidence: 84%
“…Genotype data for the COMT Val158Met SNP (rs 4680) had been generated on most previous participants using the GWAS Illumina 660K array (Stergiakouli et al., 2012). For the remainder who had not been genotyped, genotyping was performed using Snapshot single‐base extension assays (Life Technologies, Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Recent research indicates that ADHD is associated with a significant overlap of biological pathways enriched for both common variants and rare CNVs 8,10,11 , suggesting that perturbation in these pathways is critical for conferring risk to ADHD. Thus we restricted the search space for rare SNVs and InDels that may be associated with ADHD by focusing on those genes implicated in previous research.…”
Section: Gene Selectionmentioning
confidence: 99%
“…Our sample comprised 152 ADHD cases and 188 controls from amongst subjects recruited in the Republic of Ireland 11,16 . Recruitment and ascertainment of ADHD cases was approved by the Eastern Regional Health Authority research ethics committee and written informed consent was obtained from parents.…”
mentioning
confidence: 99%